Photochemistry of amido xanthonate photocages: Potential candidates for polymer-tethered photorelease of drugs - Yorke, Matthew (University of Ottawa (Canada), 2010)
Recently, photocages capable of releasing biologically relevant molecules have been reported, which utilize the rapid and efficient photodecarboxylation of 2-xanthone acetic acid (XAA) with UVA irradiation. This thesis focuses on the development of functionalized xanthonate photocages to be used for surface-tethering applications. Firstly, the preparation of amine and acetamide functionalized xanthonate (and thioxanthonate) photocage precursors will be described. Investigation into the photochemistry of the prepared derivatives led to the discovery of a solvent composition dependence on the photodecarboxylation quantum yield of acetamide derivatives. The photodecarboxylation of these derivatives occurs cleanly in the same way as XAA, but with lower efficiency. The preparation and photochemical study of acetamide functionalized photocages will then be described. Photorelease of acetate and phenylalanine demonstrated the capability of amide functionalized photocages to release biologically relevant molecules. Lastly, initial investigations into polymer tethering will be described. Attempted amide coupling through the aromatic amine led to the attachment of a short chain carboxylic acid terminated linker to modify the linking site.
Keywords: Chemistry, Organic.; Chemistry, Pharmaceutical.